An efficient token based authentication mechanism for IP trace back - S. MTech Scholar, Deepthi; P.S, Arun (International Journal of Engineering and Technology, 2018)
IP traceback plays an important role in the cyber investigation process. Because of the trusting nature of protocol the source IP address is not authenticated. So there may be the chances of occurring one way attack is very high. As a result the receiver does not accept the data properly. It is known as IP traceback problem. So the IP traceback traces the source of packets and also the traversed path of these packets. Some applications of the IP traceback are network diagnosis, path validation, performance testing and forensic analysis and so on. Objective of the paper is to prevent unauthorised users requesting from traceback information for malicious operations. So developed a token based packet marking mechanism .It uses token for identifying the sources.Â  In token based authentication IP traceback it uses a token passing mechanism. The traceback server generates the token. The data along with token is send to the end host. Only the actual data arrives at end host. The cloud based sever stores the token, data, node details and transmission details. If an attack occurs the token can be used for identifying the sources as well as traversed path of packet.Â